German Religious Emblems As Stimuli of Visual Culture in the Dutch Republic - Dietz, Feike (Church history and religious culture, 2011)
The existing studies into Dutch translations of German religious texts suggest that literary-religious culture in the Dutch Republic did not undergo significant transformation during the course of the seventeenth century as a result of German-Dutch exchange. There is even more reason to assume that German illustrated religious literature remained out of the focus of Dutch audiences: visual additions to religious texts, popular in German publications as a result of the Lutheran approach to word-image interaction, encountered resistance in the Dutch Republic where the development of illustrated religious literature was restricted and delayed compared to the Republic’s neighbouring countries. A closer look at two cases of German-Dutch literary exchange in the field of religious emblematics suggests that the restrictive Dutch visual practices were at times stimulated and innovated by the import of German models. The two cases discussed in this article give us reason to advance the very tentative hypothesis that the German-Dutch contact was at times critical to the growth of the use of religious imagery in Dutch religious literature. Finally, a case is made in favour of attending more to the international exchange of religious imagery in order to chart the impact of the Reformation in Northern Europe.